The effects of training offered in the expanded Public Works programme for youth employability at Senwamokgope Township Greater Letaba Municipality : Limpopo Province - Rabapane, Mpho Victor (University of Limpopo, 2015)
This mini-dissertation describes the research report carried out at Senwamokgope Township, Greater Letaba Municipality in Limpopo Province where a study was undertaken to investigate the effects of training offered in Expanded Public Works Programme projects on youth employability. The research is undertaken at a time in South Africa where job losses and retrenchment of employees are experienced in all sectors of government and the private sector. The South African government took a serious stance in their approach towards job creation by introducing trainings that are supposedly aimed at creating job opportunities for all citizens across the country with special attention to women and the youths. The aim of my study is to investigate whether the training offered during EPWP projects contribute to youth employability. As the researcher I therefore came up with the following questions;  What are the effects of training offered in the Expanded Public Works Programme on youth employability at Senwamokgope Township? To answer this question adequately I added sub questions. These are listed below;  How many youths according to gender are offered training?  What kind of training is been offered to youths in Expanded Public Works Programme?  How is the training contributing to employability of youths?  What are the characteristics of the youths participating in the Expanded Public Works Programme? ii This study seeks to answer the questions mentioned above. It is an attempt to determine the effects that are brought about by the intervention strategies that government engages its people in order to create work opportunities and jobs. If the effectiveness of the training can be seen it will subsequently serve the purpose of encouraging youth participation in other programmes. Data was collected through interviews. The training provider, 1 contractor, 8 youths and one official from Greater Letaba Municipality were interviewed. The data collected was then analyzed and a detailed report was drawn up with recommendations. The data was analysed using a data matrix and in conclusion the following findings were made.  All youths who went through the training are glad that they were trained .They have achieved skills which they did not have before the training.  The study has revealed that the municipality spends more money in wages on youths according to the labour force.  The effort by government through the municipality in EPWP has brought an increased number of youths in to the work environment and this has reduced the number of idle youths.  This initiative of the government has aroused confidence in the youth and they begin to aspire for greater things.  In the past years the Greater Letaba Municipality has been able to create jobs in Senwamokgope Township where youths benefitted in large numbers
Thesis (M. Ed.) -- University of Limpopo, 2016
Keywords: Extended Public Works Programme; Youth employability; Senwamokgope township; Effects of training; Employability; Unemployed youth; Youth -- Employement -- South Africa